Evaluasi Ruang Rawat Inap (Ranap) pada Bangunan Gedung Rumah Sakit Kelas D (Studi Kasus Rumah Sakit Umum Daerah Kertasari Kabupaten Bandung) - Komaludin, Kamal; Ilhamdaniah, Ilhamdaniah; Widaningsih, Lilis (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2025)
Patient care in a Class D hospital care facility involves a very important physical environment and is a crucial part of facilitating healing. Apart from that, this environment also has a significant relationship with psychological aspects that can support the acceleration of the patient's recovery process. One of the factors causing patients to experience boredom and a slow recovery process is the uncomfortable environment of the treatment area (inpatient), so that the healing process will be hampered. This study is an architectural critique of inpatient care in a built class D hospital, evaluated by the literature review that has been presented to obtain a conclusion that can be used to carry out architectural criticism in the form of recommendations or input for better architectural design work. This study uses a normative critical method with a derivative type of measurable method to analyze the structural and architectural design of inpatient rooms at the Kertasari Hospital, Bandung Regency. The results of the discussion were 72.72% in accordance with standards, 27.28% were not in accordance so they needed improvement and required quality improvement. This increase can be translated into renovation activities, or changes to the interior layout to comply with regulations, and aspects of health facility space/building requirements.